2021
DOI: 10.31224/osf.io/7azwj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urban-Scale Evaluation of Cool Pavement Impacts on the Urban Heat Island Effect and Climate Change

Abstract: We implemented a context-sensitive and prospective framework to assess the global warming potential (GWP) impacts of cool pavement strategies on specific roads for different cities. The approach incorporates several interconnections among different elements of the built environment, such as buildings and urban road segments, as well as the transportation fleet, using specific building and pavement information from an urban area. We show that increasing pavement albedo lowers urban air temperatures but can adve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…With this growth, the UHI influence, which is thought to dominate the urbanization effect on global warming, is expected to intensify (Huang et al, 2019;Yang et al, 2019). Urbanization leads to the expansion of built-up areas and increases the number of darker surfaces such as pavements and black rooftops that absorbs more radiation and intensifies UHIs and generally leads to warming the climate (He et al, 2007;Chun and Guldmann, 2014;AzariJafari et al, 2020;Xu et al, 2020). Different types of land-cover/land-use (LCLU) associated with urban expansion can influence the land-surface air temperature (LST) pattern and the magnitude of the UHI effect (He et al, 2007;Tran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With this growth, the UHI influence, which is thought to dominate the urbanization effect on global warming, is expected to intensify (Huang et al, 2019;Yang et al, 2019). Urbanization leads to the expansion of built-up areas and increases the number of darker surfaces such as pavements and black rooftops that absorbs more radiation and intensifies UHIs and generally leads to warming the climate (He et al, 2007;Chun and Guldmann, 2014;AzariJafari et al, 2020;Xu et al, 2020). Different types of land-cover/land-use (LCLU) associated with urban expansion can influence the land-surface air temperature (LST) pattern and the magnitude of the UHI effect (He et al, 2007;Tran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The development of PEMs and the enhancement of concrete durability are the strategies that can prolong the service-life performance and prevent premature failures ( 19 ). In the use phase, multiple research efforts addressed the effects of pavement–vehicle interaction on vehicle fuel consumption ( 20 22 ), urban heat island effect ( 23 ), and concrete carbonation ( 24 ), which can provide carbon offsets. Because the focus of this study was on embodied emissions, these strategies were not explicitly addressed.…”
Section: Methodsmentioning
confidence: 99%
“…Feinberg (2023) estimated that 1.1% of global warming is likely due to asphalt roads using only the average feedback factor which if brightened similar to concrete with an albedo increase of 5, could have reduced global warming by 5.5%. An MIT pavement study [36] concluded that in all U.S. urban areas, an increased temperature of 1.3°C occurs in summer months and heatwaves are 41% more intense with 50% more heatwave days due to asphalt pavements. Expansion of cities is increasing rapidly where 55% of the world's population lives and this is expected to grow to about 70% by 2050 [37].…”
Section: Natural Hotspotsmentioning
confidence: 99%
“…A primary issue in humid UHI areas is the use of black asphalt which, given the worldwide urban heatwave problems, this author feels should be banned in most cases. The warming consequences of black asphalt are not fully understood, but it is bad for the local environment and is well-documented for many problems, especially in concentrated urban areas where heatwaves cause related health issues [36,40].…”
Section: Natural Hotspotsmentioning
confidence: 99%